2018
DOI: 10.1029/2017ja025138
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Electron Heating Associated With Pulsating Auroras: Joint Optical and PFISR Observations

Abstract: In a recent study, Liang et al. (2017, https://doi.org/10.1002/2017JA024127) repeatedly identified strong electron temperature (T e ) enhancements when Swarm satellites traversed pulsating auroral patches. In this study, we use joint optical and Poker Flat Incoherent Scatter Radar (PFISR) observations to further investigate the F region plasma signatures related to pulsating auroras. On 19 March 2015 night, which contained multiple intervals of pulsating auroral activities, we identify a statistical trend, alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…The lack of observed excess redline emission suggests redline temperatures at higher altitudes are at or below what ERPA measured. We do note that the magnitude of the expected temperature enhancements below 300 km is in the range of those recently reported by Liang et al () from ground‐based studies from Poker Flat, Alaska.…”
Section: Application To Renu2 Datasupporting
confidence: 83%
“…The lack of observed excess redline emission suggests redline temperatures at higher altitudes are at or below what ERPA measured. We do note that the magnitude of the expected temperature enhancements below 300 km is in the range of those recently reported by Liang et al () from ground‐based studies from Poker Flat, Alaska.…”
Section: Application To Renu2 Datasupporting
confidence: 83%
“…These authors further suggested that ion outflow could provide the requisite cold plasma, though no observations of upflow were presented in that paper. Evidence of PFISR observations of ion upflow (not outflow) over pulsating aurora are presented by Liang et al (2018), which they attribute to the deposition of heat flux from higher altitudes that lead to the formation of an ambipolar field and subsequent ion upflow. Kenward et al (2019) also used PFISR observations, in conjunction with allsky imagers filtered at 557.7 and 630.0 nm and were able to show that the soft precipitation directly heated the electron population in the F-region.…”
Section: Ion Outflowmentioning
confidence: 99%
“…While it is still unknown how such cold plasma regions form and regulate auroral pulsation, satellite observations have shown modulating low-energy plasma fluxes that suggest to originate as plasma outflows from the ionosphere and to modulate wave growth rates Liang et al, 2015). Substantial ionization and heating in the ionosphere are associated with pulsating aurora (Hosokawa and Ogawa, 2015;Liang et al, 2018), and such processes may be the source of plasma outflow. Waves going to the southern (northern) hemisphere interact with electrons moving to the northern (southern) hemisphere.…”
Section: Driving Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al (2017; investigated the electron temperature (T e ) enhancement in the upper/topside ionosphere associated with PPAs. Based upon Swarm satellite measurements (Liang et al, 2017) and Poker Flat Incoherent Scatter Radar (PFISR) measurements (Liang et al, 2018), a strong T e enhancement in the region of PPAs is found. The pulsating auroral precipitation itself that produces the optical luminosity usually consists of ∼10 keV or even higherenergy electrons, which is ineffective in heating electrons in the upper/topside ionosphere.…”
Section: Indirect Clues Of the Possible Existence Of Low-energy Electrons Associated With Ppamentioning
confidence: 99%